The Influence of Green Skepticism on Purchase Intention in Fast Fashion in Indonesia: The Role of Brand Loyalty as a Moderator - Aldi Mahardika Lexmana; Ismail Fikri; Vania Utami Putri; Anisa Larasati (Journal Research of Social Science, Economics, and Management, 2025)
The fast fashion industry in Indonesia is rapidly growing but faces significant challenges related to environmental impacts and greenwashing, which lead to consumer skepticism about environmental claims. This research examines the influence of green skepticism on purchase intention for fast fashion products and explores the role of brand loyalty as a moderating variable in this relationship. A quantitative approach was used, with a survey design involving 385 fast fashion consumers in Indonesia, aged 18-45, selected through purposive sampling. Data were collected via an online questionnaire using a 5-point Likert scale and analyzed with Structural Equation Modeling (SEM) in SmartPLS 4.0. The results indicate that green skepticism has a significant negative effect on purchase intention (?=-0.347; t=8.924; p<0.001), meaning higher skepticism leads to lower purchase intentions. Brand loyalty was found to significantly moderate this relationship (?=0.285; t=6.173; p<0.001), with brand loyalty weakening the negative effect of skepticism. This model explains 68.4% of the variance in purchase intention, demonstrating good predictive strength. The findings suggest that greenwashing practices can backfire in an era of heightened environmental awareness, but strong brand loyalty can mitigate this negative impact. The study emphasizes the importance of authenticity and transparency in environmental communication. Fast fashion brands must build credibility through independent certification, transparent supply chains, and consistent practices. Additionally, developing and maintaining brand loyalty through product quality and effective loyalty programs is crucial to overcoming skepticism toward green claims in the fast fashion industry.